EFIKASI PENGGUNAAN SABUN BERBAHAN TRICLOCARBAN DALAM MENCUCI TANGAN - Komang Reno Sutama; Ni Made Adi Tarini (E-Jurnal Medika Udayana, 2017)
Hand hygiene had been done by using either formulated soap or handrub. This formula used to decrease the duration of hand washing compared to WHO’s duration. The aim of this study was to determine the efficacy of the Triclocarban-based soap (TCC), based on hand hygiene duration. The efficacy shown by the difference between the number of bacterial colonization after soap contact time for 10 seconds and 30 seconds as control group. Samples were taken from 24 medical students of FK UNUD, divided into 2 groups. Everyone will press both of their hands on the surface of Muller Hinton Media before and after washing hands. Total of 48 pairs of Petri dish were collected. Total of 8 pairs of the Petri dish were issued, for allegedly contaminated. Mean and SD before washing hands from group A (10 second) was 127 ± 79.416 CFU and group B (30 second) was 92.40 ± 40.735 CFU. The mean and SD after washing the hands of group A was 44.80 ± 28.268 CFU and group B was 63.80 ± 55.994 CFU. There was significant difference in colonies number in group A with Triclocarban-based soap (p = 0.012, paired t-test), as well as in group B (p = 0.025, paired t-test). Whereas compared between the two groups, there is no significant difference in number of bacterial colonies (p = 0.351, Independent T-test). In conclusion the efficacy of TCC-based soap between 10 seconds and 30 seconds hand washing had no significant different.Keywords: Hand Hygiene, Contact Time, Number of Colonies of Bacteria